Swarm and swim motilities of salmonella enterica serovar typhimurium and role of osmoregulated periplasmic glucans - Dharne, Mahesh S.; Kannan, Porteen; Murphy, Charles; Smith, Allen; Bhagwat, Arvind A. (Microbiol Discov, 2015)

Size does matter: antibacterial activities and cytotoxic evaluation of polymorphic CuO nanostructures - Desai, Dnyanada G.; Navale, Govinda R.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Materials Science, 2023)
Nanostructured materials play a significant role in antibacterial activities. However, understanding the geometrical influence at the nanoscale in terms of size- and shape-correlated physical properties on antibacterial activities is very essential. Herein, we report the antibacterial influence of various copper oxide nanostructures (CuO NS) such as nanoparticles (NPs) (< 10 nm), nanospheres (NSs) (50-100 nm), and porous nanoflowers (NFs) (asymptotic to 350 nm). The XRD confirmed the crystalline nature of CuO NPs without impurities. The antibacterial activities of CuO NPs were investigated by the microplate dilution method and confocal laser scanning microscopic (CLSM) imaging. NPs having a diameter less than 10 nm exhibited significant damage to the bacterial cell membrane than NSs and NFs. Interestingly, NPs illustrated relatively low antibacterial activity against Gram-negative bacteria (Pseudomonas aeruginosa and Acinetobacter baumannii) than Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis). Acinetobacter baumannii was found to be more susceptible to the NPs than other bacterial strains, attributed to its increased membrane permeability. The death phase was observed at a concentration of 15.6 mu g mL(-1) and 3.9 mu g mL(-1) for P. aeruginosa and A. baumannii, respectively, when treated with CuO NP after the 8 h of incubation. Similarly, for S. aureus and S. epidermidis, the death phase was observed at the concentration of 31.2 mu g mL(-1) and 250 mu g mL(-1), respectively. Furthermore, as the cell cytotoxicity measurements against human fibroblast L9239 cells revealed that CuO NPs were safe. The morphological and cell viability assay demonstrated 100% cell survival, when treated with NPs and NSs (5, 10, and 25 mu g mL(-1)), signifies no cytotoxicity. Therefore, CuO nanoparticles can be used for clinical and therapeutic applications.

Sustainable and cleaner production of poly-gamma-glutamic acid (γ-PGA) biopolymer using floral waste and its anti-staling properties - Nair, Pranav G.; Dharne, Mahesh S. (Journal of Cleaner Production, 2023)
The framework of sustainable development (SD) hinges on 17 different ideals established by the United Nations. This call for SD can be addressed by the circular bio-economy concept, which not only ensures effective waste management but also encourages its valorization and repurposing, hence fostering both ecological and economic stability. One-third of the world's floral production is in jeopardy, and because there are no potential solutions for sustaining floral waste, it inevitably ends up in landfills and riverine systems, which is detrimental to the environment. Therefore, in the present study, floral waste that was destined for landfills or water bodies was productively valorized to poly gamma glutamic acid (gamma-PGA), a high value biopolymer, with a yield of 40 g/L and productivity of 1.6 g/L/h employing an L-glutamic acid (L-GA) independent feeding approach. When gamma-PGA was coated onto Vitis vinifera grapes, it exhibited excellent moisture retention, reduced microbial contamination, and preserved the grapes' aesthetic characteristics and nutrient content. The weight loss study demonstrated that grapes coated with 1% and 2% gamma-PGA experienced significantly lower weight loss (13% and 14% respectively) compared to the control group (21.6%). Moreover, a 5-min dip coating time proved to be the most effective in reducing weight loss to 12.43%. Over a period of 14 days, the control group exhibited a remarkably high weight loss (41%) in contrast to the treated group, which showed significantly lower weight loss (16%). Our work is a fine example of how the circular bio-economy and waste valorization may be used to achieve the long-term objectives of sustainable development, economic stability, and food security.
Keywords: Bio-economy; Floral waste; L-GA independent; Poly-gamma-glutamic acid; Valorization

Strain improvement for cellulolytic enzymes for effective saccharification of lignocellulosic biomass by mutant of Penicillium funiculosum NCIM 1228 - Chavan, Sambhaji; Shete, Ashvini; Dharne, Mahesh S. (Systems Microbiology and Biomanufacturing, 2024)
Lignocellulosic biomass (LCB) generated from various agro-waste can be effectively used to manufacture a broad range of value-added products cost-effectively. However, the high cost of cellulases is still a major challenge in producing biofuels and biochemicals from LCB on an industrial scale. The enzyme output and activity of cellulase in the fermentation broth are closely linked in terms of enzyme manufacturing costs. Therefore, research on efficient fermentation processes of hyperactive fungi, and cost-effective recovery systems have been directed toward lowering enzyme costs and increasing overall enzyme production. Penicillium funiculosum NCIM 1228 (P. funiculosum NCIM 1228) is a feasible cellulase-producing strain that possesses all four enzymes required to efficiently hydrolyse LCB. The primary objective of this study was to employ random mutagenesis to increase enzymes titer, yield, and productivity. The potential mutant D4 (derived by Ethyl methanesulfonate (EMS) mutation) exhibited 6.47, 3.05, 3.03, and 3.19-fold higher activities of FPase, CMCase, β-glucosidase, and xylanase, respectively, compared to the parent strain. Mutant D4 demonstrated a promising protein titer of 17.96 g/L at the 40 L fermenter scale, with productivities of 479, 4249, and 6987 U/L/day for FPase, CMCase, and Xylanase, respectively, on the tenth day. Interestingly, the crude form of enzymes from the mutant demonstrated promising saccharification, releasing 3.54% of glucose and achieving a 54.03% of cellulose conversion efficiency without formulation. In comparison, a commercially formulated enzyme exhibited 53.07% efficiency against pre-treated sugarcane bagasse, indicating its promising potential for future applications.